PENERAPAN METODE EXPONENTIAL SMOOTHING WINTER DALAM SISTEM INFORMASI PENGENDALIAN PERSEDIAAN PRODUK DAN BAHAN BAKU SEBUAH CAFE - Wahyu Pramita; Haryanto Tanuwijaya (Jurusan Teknik Informatika, 2010)
Effect of fluctuations in food and beverage sales that is not uniform in a cafe can be a problem determining the raw material and raw material purchase to the supplier. This problem resulted in a surplus or shortage of raw materials. Unused raw materials must be removed for exceeding the period expires, whereas raw material shortages caused cafe can’t fill all customer orders. Application of Exponential Smoothing method Winter in the inventory control information system products and raw materials aim to resolve these problems. Winters Exponential Smoothing method for forecasting data characteristics tend to be stationary and have a seasonal pattern at a time trend. This information system to produce forecasts to predict a certain product sales in future periods. By comparing the measurement error is the smallest value of MAPE and MSE, then the system will generate forecasting information that is used to determine the optimum amount of raw materials ordering one next period. Research also yields a percentage value of forecasting to the actual data to determine the accuracy of forecasting of raw material at the cafe. This research to optimally control the raw material for the success of customer service in a cafe.